2020
DOI: 10.1002/jcb.29858
|View full text |Cite
|
Sign up to set email alerts
|

Mps1 controls spindle assembly, SAC, and DNA repair in the first cleavage of mouse early embryos

Abstract: Monopolar spindle-1 (Mps1) is a critical interphase regulator that also involves into the spindle assembly checkpoint for the cell cycle control in both mitosis and meiosis. However, the functions of Mps1 during mouse early embryo development is still unclear. In this study, we reported the important roles of Mps1 in the first cleavage of mouse embryos. Our data indicated that the loss of Mps1 activity caused precocious cleavage of zygotes to 2-cell embryos; however, prolonged culture disturbed the early embry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…In our experiments, we used reversine, a potent Mps1 kinase inhibitor ( Santaguida et al, 2010 ). Previously published results using different inhibitors showed that in zygotes, Mps1 inhibition negatively impacts chromosome segregation and compromises further development ( Ju et al, 2021 ). In our experiments, we observed a much stronger effect.…”
Section: Discussionmentioning
confidence: 99%
“…In our experiments, we used reversine, a potent Mps1 kinase inhibitor ( Santaguida et al, 2010 ). Previously published results using different inhibitors showed that in zygotes, Mps1 inhibition negatively impacts chromosome segregation and compromises further development ( Ju et al, 2021 ). In our experiments, we observed a much stronger effect.…”
Section: Discussionmentioning
confidence: 99%